Determination of Value : Appraisal Guidance on Developing and Supporting a Credible Opinion. - Rosillo, Frank (Wiley, 2013)
How to develop and support a credible opinion of value based on a foundational framework This book provides knowledge and guidance to valuation practitioners on achieving a new level of professionalism and credibility, as well as to those stakeholders in the valuation process in need of assessing the credibility of an appraiser's work product for decision-making purposes. It introduces a well defined framework of key credibility concepts and procedures at each step of the appraisal process, including reasonableness tests, valuation methodologies, financial analysis, economic and indus.